2015
DOI: 10.1080/21548331.2015.1023159
|View full text |Cite
|
Sign up to set email alerts
|

Effective inpatient medication reconciliation: The 10 commandments

Abstract: Medication Reconciliation (MedRec) is the comprehensive process of medication verification, clarification and documentation in an effort to avoid medication errors. There are many reasons that contribute to the inadequacies of current day inpatient MedRec. Among these include the limited medical literacy of patients, communication between providers and teams of providers, and the intrinsic difficulties of medical charting. Although the best approach to inpatient MedRec is not known, the following outlines the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Overall, most nurses in our study perceived they had a minor role in medication reconciliation at hospital discharge with pharmacists and doctors having a major role. Some were unclear about their Nurses reported medication reconciliation at hospital discharge was a complex process involving numerous clinicians who completed similar tasks such as patient education (Penm et al, 2019;Siu, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, most nurses in our study perceived they had a minor role in medication reconciliation at hospital discharge with pharmacists and doctors having a major role. Some were unclear about their Nurses reported medication reconciliation at hospital discharge was a complex process involving numerous clinicians who completed similar tasks such as patient education (Penm et al, 2019;Siu, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Nurses reported medication reconciliation at hospital discharge was a complex process involving numerous clinicians who completed similar tasks such as patient education (Penm et al, 2019; Siu, 2015). Confirming previous research (Aires‐Moreno et al, 2020; Athuraliya et al, 2017), nurses in our study identified medication discrepancies, checked the accuracy of discharge medications, delivered patient education, and coordinated the healthcare team to ensure patient safety and avoid discharge delays.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If there is no clear role designation, the ultimate responsibility of reporting falls on departmental leadership. 3 Delays in reporting (option 4) slow the improvement process. After an incident report is created, the hospital's quality team determines the incident severity.…”
Section: Consider the Optionsmentioning
confidence: 99%
“… Define the terms 'medication' and 'reconciliation' to ensure uniformity with the medication reconciliation process (i.e., what constitutes a medication and what processes are encompassed by reconciliation) (Greenwald et al, 2010).  Define the varying roles of the multidisciplinary participants in the reconciliation process (Greenwald et al, 2010;Siu, 2015).  Enhance the accuracy of medication reconciliation with pharmacist involvement or pharmacist-related interventions (Mergenhagen et al, 2012;Mueller, Sponsler, Kripalani, & Schnipper, 2012).…”
Section: Medication Reconciliationmentioning
confidence: 99%